Uncovering cultural values at the Wiraraja monument as a reflection of the Mojokerto community's character - Virda Oktafianti Maqviro; Sony Sukmawan (Universitas Muhammadiyah Malang, 2025)
The Wiraraja monument holds significant historical and symbolic value, representing the character of the local community. This research aims to elucidate the cultural value embodied in the Wiraraja monument located in The town square Kota Mojokerto to understand the character of the Mojokerto people as symbolised by the monument. This study employed a qualitative methodology with an interpretative approach to the surrounding environment. Data were collected through interviews, observations, and visual documentation. The interviews were conducted in depth. The exploration of cultural values is grounded in C. Kluckhohn's theory, which categorizes fundamental cultural values into two main categories. Kluckhohn further divides these basic life values into five components: 1) Human nature, 2) Human work, 3) Human interaction with space and time, 4) Human interaction with the surrounding nature, and 5) Human interaction with neighbors. The findings of this study identified several architectural elements that reflect cultural values, including building concepts, lotus elements, monument bodies, allegorical reliefs, and systematic dimensions. Additionally, the research delineates the character of the Mojokerto community (within the Surabaya sub-ethnic group), which reflects the local cultural heritage, particularly the traits of being religious, hardworking, fair and balanced, respectful of ancestors, environmentally conscious, and respectful of leaders. This study is anticipated to serve as a reference for planning public spaces with consideration of local cultural identity. Tugu Wiraraja merupakan monumen yang memiliki nilai historis dan simbolik dalam merepresentasikan karakter masyarakat setempat. Penelitian ini bertujuan mendeskripsikan nilai budaya dalam bangunan tugu Wiraraja yang terletak di Alun alun Kota Mojokerto, untuk mengetahui karakter masyarakat Mojokerto dalam simbolisasi Tugu Wiraraja. Penelitian uini menggunakan metode kualitatif dengan pendekatan interpretatif terhadap lingkungan sekitar Pengumpulan data dalam penelitian ini dilakukan dengan cara wawancara, observasi, dan dokumentasi visual. Wawancara dilakukan secara mendalam (in-depth interview). Sedangkan penelusuran nilai nilai budaya didasarkan pada teori C. Kluckhohn yang membagi pokok nilai dasar dalam kehidupan menjadi lima bagian, yakni: 1) Hakikat manusia, 2) Karya manusia, 3) Manusia dengan ruang dan waktu, 4) Manusia dengan alam sekitar, 5) Manusia dengan sesamanya. Hasil penelitian ini mengidentifikasi beberapa unsur bangunan yang mencerminkan nilai-nilai budaya, termasuk konsep bangunan, elemen teratai, badan tugu, relief alegoris, dan sistematika ukuran bangunan. Penelitian ini juga menggambarkan karakter masyarakat Mojokerto (dalam sub-etnik Surabaya) yang mencerminkan warisan budaya lokal, terutama sikap religius, pekerja keras, berlaku adil dan seimbang, menghormati leluhur, peduli terhadap lingkungan, serta menghormati pemimpin. Penelitian ini diharapkan dapat memberikan kontribusi sebagai acuan dalam perencanaan ruang publik dengan memperhatikan identitas budaya lokal.